Pendampingan Pelatihan Kepemimpinan Pengurus Asrama Pondok Pesantren Sunan Drajat Paciran Lamongan - Sunaji, Sunaji (Jaanur ElBarik Indonesia, 2025)
This community mentoring activity aims to improve the managerial and leadership quality of dormitory administrators. This program is designed to equip administrators with the knowledge and skills needed to manage the dormitory effectively and efficiently, as well as create a conducive environment for students. The methods used in this training include lectures, group discussions, case studies, and simulations. The training materials cover various aspects of leadership, such as effective communication, decision-making, conflict management, and motivation. The results of this activity show a significant increase in the understanding and leadership skills of students. Dormitory administrators reported increased self-confidence in carrying out their duties, as well as better abilities in facing daily challenges. It is hoped that through this program, the Sunan Drajat Islamic Boarding School can produce more professional and dedicated dormitory administrators, so that they can support the achievement of the vision and mission of the Islamic boarding school as a whole.